DESAIN HALTE BIS SURABAYA DENGAN TEMA IKONIK - Yohanes Firananta Setyo Atmono (Indonesian Society of Applied Science, 2021)
Bus shelter for public transport in Surabaya has been made to accommodate the needs of the Department of Transportation and government city. This facilities built to attract public interest to using public transportation. Currently, several shelter Surabaya Bus have been built, but the existing conditions of the bus stops have not met the requirements. Therefore it is necessary to design a Surabaya bus stop that offers convenience, security and most importantly introduces the city of Surabaya both for tourist purposes and for city branding. There is a need for shelters that are designed aesthetically, comfortably and the most important thing is that users feel safe when they are at bus stops. Designed by paying attention to the overall design principles, namely the character of the user, both disabled and normal, user activities and support facilities. Exterior and interior bus shelter concept design use tropical and iconic ornaments from Surabaya iconic places